Hydrogen evolution and consumption in AOT–isooctane reverse micelles by Desulfovibrio gigas hydrogenase - Moura, José J. G. (2008)
The enzyme hydrogenase isolated from the sulphate reducing anaerobic bacterium Desulfovibrio gigas was encapsulated in reverse micelles of AOT–water–isooctane. The enzyme ability to consume molecular hydrogen was studied as a function of the micelle size (given by Wo = [H2O]/[organic solvent]). A peak of catalytic activity was obtained for Wo = 18, a micelle size theoretically fitting the heterodimeric hydrogenase molecule. At this Wo value, the recorded catalytic activity was slightly higher than in a buffer system(Kcat = 169.43 s−1 against the buffer value of 151 s−1). The optimal buffer used to encapsulate the enzyme was found to be imidazole 50 mM, pH 9.0. The molecular hydrogen production activity was also tested in this reverse micelle medium.